Development of Animated Video-Based Teaching Materials for SKI Subjects for Class V MI Tarbiyatul Athfal Sera Tengah Bluto Sumenep - Iik Timamah; Faridatul Jannah; Faiqatul Munawwarah; Nurul Zainab (COMPETITIVE: Journal of Education, 2024)
This study aims to develop animated video-based teaching materials for the subject of Islamic Cultural History (SKI) for grade V at MI Tarbiyatul Athfal Sera Tengah Bluto Sumenep using Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This study was conducted to overcome the limitations of conventional teaching materials that are less interesting and interactive. The trial involved 7 grade V students and validation was carried out by teaching material experts and language experts to ensure the quality and clarity of the material. The validation results by language experts showed an average value of 4 out of 4, while the teaching material experts provided several revisions before the teaching materials were declared valid. Data analysis through pre-test and post-test as well as questionnaires showed a significant increase in student understanding after using animated video-based teaching materials. As many as 90% of students found it easier to understand the material, and teachers stated that this teaching material was very helpful in learning. The revisions made included adding visual illustrations, improving voice narration, and optimizing video duration. The final product shows very good criteria with an average score of 3.5 out of 4 in terms of material clarity, animation quality, and student engagement.